2016
DOI: 10.1159/000449527
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Pre- and Postoperative Anti-p53 Antibody Levels in Colorectal Cancer Patients: A Retrospective Study

Abstract: Objective: To determine the utility of the post-/preoperative anti-p53 antibody (p53 Ab) ratio as a prognostic factor for colorectal cancer (CRC) recurrence. Methods: A total of 737 nonmetastatic CRC patients who had undergone R0 resection were retrospectively analyzed. p53 Ab levels were measured within 1 month prior to and at least every 3 months after surgery. Post-/preoperative p53 Ab ratios were calculated, and the optimal ratio cutoff values for predicting recurrence were determined using the Kaplan-Meie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The controversial clinical issue related to serum p53-Ab lies in the relatively low incidence of seropositivity in patients with CRC. While esophageal cancer or head and neck cancers are reportedly associated with relatively higher rate of seropositivity ([ 30%) of p53-Ab, [7] serum p53-Ab is less frequent (20%-45%) in CRC patients [8,9,12,13] and the seropositivity rate for p53-Ab (29%) in the current study was consistent with these results. However, one of the noteworthy results of the present study is that there seemed to be a correlation between the serum preoperative p53-Ab level and the likelihood of postoperative seropositivity for p53-Ab in patients undergoing resection of CLMs (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The controversial clinical issue related to serum p53-Ab lies in the relatively low incidence of seropositivity in patients with CRC. While esophageal cancer or head and neck cancers are reportedly associated with relatively higher rate of seropositivity ([ 30%) of p53-Ab, [7] serum p53-Ab is less frequent (20%-45%) in CRC patients [8,9,12,13] and the seropositivity rate for p53-Ab (29%) in the current study was consistent with these results. However, one of the noteworthy results of the present study is that there seemed to be a correlation between the serum preoperative p53-Ab level and the likelihood of postoperative seropositivity for p53-Ab in patients undergoing resection of CLMs (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Until date, conflicting results have been reported in regard to the clinical significance of p53‐Ab in CRC patients. While several authors reported that a higher preoperative p53‐Ab level is an independent risk factor for recurrence after resection of primary CRC, [8, 9, 11] Abe et al and Tang et al [12, 13] reported that preoperative seropositivity for p53‐Ab by itself was not a reliable prognostic factor. However, these same authors also reported that persistent seropositivity for p53‐Ab or a delayed decrease in the serum p53‐Ab level after surgery might be associated with a higher risk of recurrence in CRC patients.…”
Section: Discussionmentioning
confidence: 99%